Ornithine decarboxylase and polyamines in familial adenomatous polyposis - GIARDIELLO, F. M; HAMILTON, S. R; HYLIND, L. M; YANG, V. W; TAMEZ, P; CASERO, R. A (Cancer research (Chicago, Ill.), 1997)
Familial adenomatous polyposis (FAP), due to germ-line mutation of the adenomatous polyposis coli (APC) gene, is characterized by development of colorectal adenomas and ultimately colorectal cancer. The usefulness of ornithine decarboxylase (ODC) activity and polyamine levels in normal-appearing colorectal mucosa to stratify risk for colorectal neoplasia by discriminating presymptomatic individuals with germ-line APC mutation (genotype-positive) from genotype-negative family controls was evaluated in 36 at-risk subjects undergoing endoscopic and genetic screening for FAP. ODC activity and levels of putrescine, spermidine, and spermine were significantly higher in presymptomatic genotype-positive patients compared to genotype-negative persons (P = 0.029, <0.001, 0.002, and <0.001, respectively). Moreover, a putrescine level with a cutoff point of 1.5 nmol/mg protein was the most accurate single discriminator of risk status. ODC activity and polyamine levels are significantly elevated in gene carriers of FAP before the development of polyposis, suggesting a role for these compounds in tumorigenesis of FAP. These assays may be useful in evaluating at-risk members of FAP families in which mutation of the APC gene cannot be found.